A formação do enfermeiro na reflexividade - Almeida Júnior, José Jailson de (2013)
The study proposes an understanding of nurses training in reflexivity and the overcome the limits of biomedical formation model, from the thought of John Dewey, inserted in the panorama of the reflective practitioner introduced by Donald Schön and dialoguing with the perspective of the transforming action of Paulo Freire. We used a qualitative approach to collect empirical data through focus groups conducted with nursing students from 3rd to 5th year in the Faculty of Health Sciences, Trairi / UFRN in the year 2012. Data analysis occurred through the technique of thematic content analysis constituted of three stages: pre-analysis, exploration of the material, treatment of results, inference and interpretation of the material. Thus, the categories formulated by organizing, classifying and aggregating the the content of the speeches to groups who shared opinions approximations of thought generating a set of categories of analysis designed from the contents. The results present the experiences of nursing students and their reflections, demonstrating that the process of reflection permeates the journey of life. It is inferred that the knowledge acquired in these experiences do not always participate in this dialogue in this formative process, reducing previous experiences in the field of exemplification of everyday situations. We conclude that it is necessary to consolidate innovative pedagogical proposals that allow the continuous dialogue with reality, breaking with the decontextualized teaching process from reality insertion of the university. Rethinking of the structures is recommended, reinforcing the break with the biomedical model and the integration of knowledge dynamically